2000
DOI: 10.1084/jem.192.10.1479
|View full text |Cite
|
Sign up to set email alerts
|

Hematopoietic Expression of Hoxb4 Is Regulated in Normal and Leukemic Stem Cells through Transcriptional Activation of the Hoxb4 Promoter by Upstream Stimulating Factor (Usf)-1 and Usf-2

Abstract: The homeobox genes encode a family of transcription factors that regulate development and postnatal tissue homeostasis. Since HOXB4 plays a key role in regulating the balance between hematopoietic stem cell renewal and differentiation, we studied the molecular regulation of HOXB4 expression in human hematopoietic stem cells. HOXB4 expression in K562 cells is regulated at the level of transcription, and transient transfection defines primary HOXB4 regulatory sequences within a 99-bp 5′ promoter. Culture of high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
46
0
6

Year Published

2002
2002
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(55 citation statements)
references
References 45 publications
(57 reference statements)
3
46
0
6
Order By: Relevance
“…In agreement with this, USF-1 or USF-2 knockout mice have a diminished glucose response (21) and fatty acid synthase expression (22). Other genes such as follicle-stimulating hormone receptor (23), metallothionein (24), HOXB4 transcription factor (25), and the class II major histocompatibility complex (26) are regulated by USF-1. Additionally, USF overexpression has been found to inhibit growth in a number of cancer cell lines (27,28).…”
supporting
confidence: 51%
“…In agreement with this, USF-1 or USF-2 knockout mice have a diminished glucose response (21) and fatty acid synthase expression (22). Other genes such as follicle-stimulating hormone receptor (23), metallothionein (24), HOXB4 transcription factor (25), and the class II major histocompatibility complex (26) are regulated by USF-1. Additionally, USF overexpression has been found to inhibit growth in a number of cancer cell lines (27,28).…”
supporting
confidence: 51%
“…TPO simulation of HSCs activates MAPK, which we and others have shown leads to induction of HOXB4 expression in both normal and K562 cells (6,27). Although a pivotal role of NF-Ya in TPO-induced HOXB4 activation is not yet known, MEK activation has itself been shown to up-regulate NF-Ya activity functioning on the promoter of other NF-Ya target genes such as GADD45 (28).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, we demonstrated that the trimeric transcription factor NF-Y activates the HOXB4 promoter in cooperation with upstream͞ubiquitous stimulating factor 1 and 2 (USF1͞2) in normal and malignant hematopoietic cells (6,7). Studies from other laboratories suggested that NF-Y is also a potent inducer for numerous other genes whose function likely influences stem cell (SC) function, including HOXB7, JunB, p27, CDK1, MDR1, and TGF␤R-II (8)(9)(10)(11)(12)(13).…”
mentioning
confidence: 99%
“…Recently, the two essential DNA binding sites were identi®ed in the promoter region of HoxB4 gene functioning in both normal and malignant hematopoietic primitive cells, just upstream of its transcriptional starting site. One of them was a classical E box and served as the functional binding site for USF1 and USF2 (Giannola et al, 2000).…”
Section: Homeobox Genesmentioning
confidence: 99%